“We” the Refugees: Reflections on Refugee Labels and Identities - Vigil, Yanery Navarro; Baillie Abidi, Catherine (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2018)
In this article the authors present an auto-ethnographical analysis, describing their personal experiences with forced migration. Using narrative passages, the authors problematize the way in which refugee identities are entwined with socially constructed labels. The authors explore the points at which self-identifcation negotiates with labelling in order to create new spaces wherein individual and collective refugee experiences mutually shape and transform each other. These new spaces emerge from an inclusive participatory socio-cultural and political process where the idea of “us” and “them” merges into a “we.” This article represents the culmination of the authors’ sustained interactions (in conversation, in storytelling, in shared analyses, in writing) and serves as an example of putting a new space into action.